PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SMP IT AL-HIJRAH - Khazanah Khazanah; Asrin Lubis (MES: Journal of Mathematics Education and Science, 2026)
This study aims to determine: efforts that can be made to improve students' mathematical concept comprehension abilities and the extent of improvement in students' mathematical concept comprehension abilities through the application of the STAD cooperative learning model assisted by GeoGebra. This study is a classroom action research conducted in two cycles. The research subjects were 28 students in class VIII-D of SMP IT Al-Hijrah in the 2024/2025 academic year, where the researcher acted as the teacher during the learning process. The research instruments included tests, observations, and interviews. The results showed that the application of the STAD cooperative learning model assisted by GeoGebra could improve students' mathematical concept comprehension skills through the provision of contextual examples, guided discussions with prompts and questions, additional exercises, facilitation of the use of GeoGebra to visualise concepts, systematic guidance on the steps to solve problems, reinforcement and motivation, and rewards for active groups. Based on the test results, there was an increase in conceptual understanding ability from the pre-cycle, where only 11 students (39%) achieved mastery with an average score of 51.79, to 17 students (61%) in cycle I with an average score of 68.45 and an N -Gain of 0.20 (low category), and in cycle II, it increased to 24 students (86%) with an average score of 85.71 and an N-Gain of 0.59 (medium category). Thus, the application of the STAD cooperative learning model assisted by GeoGebra proved to have a significant positive impact on the mathematical concept comprehension abilities of Grade VIII students at SMP IT Al-Hijrah.